Effectiveness of red yeast rice on carotid atherosclerosis: A systematic review and meta-analysis - Wang, Shuai; Chen, Yue; Wang, Rui; Ma, Bailing; Wang, Zhenzhen; Tang, Guanguang; Wang, Siyu; He, Yi; Qu, Liping (Frontiers in Pharmacology, 2022)
While several studies have demonstrated the preventive and therapeutic effects of red yeast rice (RYR), a traditional Chinese medicine, on carotid atherosclerosis through the reduction of low-density lipoprotein cholesterol (LDL-C) level and other risk factors, the evidence remains inconsistent. This study aimed to further evaluate the effects of RYR in carotid atherosclerosis. Several databases were searched for original trials of RYR for the treatment of carotid atherosclerosis that reported plaque indicators. Carotid plaque area (AREA), carotid plaque score (SCORE), and intima-media thickness (IMT) were set as the primary outcomes, while lipid profile and safety indicators were set as the secondary outcomes. Meta-analyses were performed on the randomized controlled trials (RCTs) using Comprehensive Meta-analysis software. Heterogeneity was evaluated using the I2 index and Q statistic. Subgroup, sensitivity, and dose-effect analyses were conducted. Twenty RCTs with 2217 patients were included. Compared to the control group, AREA (SMD = −0.855, 95%CI: −1.259 to −0.451, p < 0.001), IMT (SMD = −0.588, 95%CI: −0.792 to −0.384, p < 0.001), SCORE (SMD = −0.708, 95%CI: −1.135 to −0.282, p = 0.001), LDL-C (SMD = −0.938, 95%CI: −1.375 to −0.502, p < 0.001), triglyceride (SMD = −0.766, 95%CI: −0.980 to −0.551, p < 0.001), and total cholesterol (SMD = −0.858, 95%CI: −1.254 to −0.462, p < 0.001) were significantly decreased and HDL-C (SMD = 0.389, 95%CI: 0.044–0.733, p = 0.027) was significantly increased following RYR therapy. The indicators for safety were not significant and did not differ between the two groups (p > 0.050). Heterogeneities mainly existed for the treatment time or control group setting. Most results showed no changes in the sensitivity analysis. Dose-effect relationships were observed for all indicators except for TC and HDL-C. We concluded that RYR therapy showed considerable efficacy and an acceptable safety profile for the treatment of carotid atherosclerosis in the Chinese population.